Novel insights into the localization and functions of tripartite motif-containing 22 - Gayathri, Sivaramakrishnan (2008)
Tripartite motif-containing 22 (TRIM22) is an interferon (IFN)- and p53-inducible gene product previously shown to possess antiviral and growth inhibitory properties. Microarray analyses in progesterone receptor-positive and estrogen receptor-negative breast cancer cells (ABC28) revealed that progesterone dramatically enhances levels of the TRIM22 transcript. Since progesterone inhibits the growth of breast cancer cells, the aim of this study was to generate specific antibodies against TRIM22, to investigate TRIM22’s function, and to investigate if TRIM22 mediated progesterone’s growth inhibitory effect in breast cancer cells.